Déjà Vu: An Illusion of Prediction - Cleary, Anne M.; Claxton, Alexander B. (Psychological Science, 2018)
Déjà vu is beginning to be scientifically understood as a memory phenomenon. Despite recent scientific advances, a remaining puzzle is the purported association between déjà vu and feelings of premonition. Building on research showing that déjà vu can be driven by an unrecalled memory of a past experience that relates to the current situation, we sought evidence of memory-based predictive ability during déjà vu states. Déjà vu did not lead to above-chance ability to predict the next turn in a navigational path resembling a previously experienced but unrecalled path (although such resemblance increased reports of déjà vu). However, déjà vu states were accompanied by increased feelings of knowing the direction of the next turn. The results suggest that feelings of premonition during déjà vu occur and can be illusory. Metacognitive bias brought on by the state itself may explain the peculiar association between déjà vu and the feeling of premonition.